Organic functionalization of carbon nanotubes - Georgakilas, Vasilios; Kordatos, Konstantinos; Prato, Maurizio; Guldi, Dirk Michael; Holzinger, Michael; Hirsch, Andreas (Journal of the American Chemical Society, 2002)
A very general and versatile method for functionalizing different types of carbon nanotubes is described, using the 1,3-dipolar cycloaddition of azomethine ylides. Approximately one organic group per 100 carbon atoms of the nanotube is introduced, to yield remakably soluble bundles of nanotubes, as seen in transmission electron micrographs. The solubilization of the nanotubes generates a novel, interesting class of materials, which combines the properties of the nanotubes and the organic moiety, thus offering new opportunities for applications in materials science, including the preparation of nanocomposites. Copyright © 2002 American Chemical Society.